A panorama of colon cancer in the era of liquid biopsy - Sylvie Devalle; Veronica Aran; Cesar de Souza Bastos Júnior; Vera Lucia Pannain; Paulo Brackmann; Marcelo Leal Gregório; José Eduardo Ferreira Manso; Vivaldo Moura Neto (The Journal of Liquid Biopsy)
Colon cancer (CC) is one of the most frequent cancers worldwide being responsible for over 500 thousand deaths in 2022. Its financial and human burden is expected to increase in the next decades accompanying the growing and aging of the global population. Much of this burden could be alleviated considering that the lethality of CC is mostly due to its late diagnosis and failure in the individualized management of patients. Coordinated government actions and implementation of better diagnostic tools capable of detecting CC earlier and of tracking tumoral evolution are mandatory to achieve a reduction in CC's social impact. CtDNA-based liquid biopsy (LB) has great potential to contribute to patients' screening adhesion, CC earlier detection, and to longitudinal tumor follow-up. In this review, we will discuss the latest epidemiological data on CC disease, diagnostic, subtypes, genetics, and treatment management focusing on the advantages and limitations of ctDNA-based LB, including important bottlenecks and solutions necessary for its clinical translation. The latest ctDNA-directed CC clinical trials will also be examined.